2016
DOI: 10.1371/journal.pone.0168609
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Lipophilic Constituents in the Skin of Migratory Adult Sea Lamprey from the Great Lakes Region

Abstract: The sea lamprey (Petromzons marinus) is an invasive ectoparasite of large-bodied fishes that adversely affects the fishing industry and ecology of the Laurentian Great Lakes. Lipid content in the whole sea lamprey and muscles, liver and kidney of metamorphosing larval stages has been reported. Similarly, the fatty acid profile of the rope tissues of sexually-mature male sea lampreys has also been reported. The average body weight of a sub-adult migratory sea lamprey is 250 g, which includes 14.4% skin (36 g). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 57 publications
(85 reference statements)
0
18
2
Order By: Relevance
“…Festuca arundinacea, Lolium perenne , and Phleum pratense ) and there was no difference in mean digestibility between grasses and legumes. Care must be taken to consider the full suite of nutritive metrics, including their positive or negative effects on overall plant productivity, when selecting species for use as livestock or wild herbivore feed (Wagner et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Festuca arundinacea, Lolium perenne , and Phleum pratense ) and there was no difference in mean digestibility between grasses and legumes. Care must be taken to consider the full suite of nutritive metrics, including their positive or negative effects on overall plant productivity, when selecting species for use as livestock or wild herbivore feed (Wagner et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this evidence we hypothesize the sea lamprey alarm cue contains water soluble nitrogenous compounds that are emitted from damaged skin that induce anti-predator behavior in migrating sea lamprey. In this study, we characterize the nitrogenous compounds contained in a previously reported aqueous ethanolic Soxhlet extract from lamprey skin that contains the repellent molecules [12,13,53]. First, we separated the extract into chloroform-soluble and chloroform-insoluble fractions; the chloroform-soluble fraction exhibits no behavioral reactivity and contains cholesterol esters, tri- and di-glycerides, cholesterol, free fatty acids and minor amounts of environmental pollutants [53].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we characterize the nitrogenous compounds contained in a previously reported aqueous ethanolic Soxhlet extract from lamprey skin that contains the repellent molecules [12,13,53]. First, we separated the extract into chloroform-soluble and chloroform-insoluble fractions; the chloroform-soluble fraction exhibits no behavioral reactivity and contains cholesterol esters, tri- and di-glycerides, cholesterol, free fatty acids and minor amounts of environmental pollutants [53]. We report evidence that the alarm cue is contained in the water-soluble (chloroform-insoluble) fraction and proceeded to fractionate, purify, and chemically characterize the major nitrogenous compounds that compose this mixture.…”
Section: Introductionmentioning
confidence: 99%
“…A rapidly expanding body of advanced climate [ 46 ] and global energy-use data [ 7 ] has firmly established the urgent need for strategic leadership and action on CO 2 emissions reductions. Failure to deliver this is forecast to influence the future for centuries, if not millennia [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced microalgae-based renewable fuel systems have significant potential to address these needs and to support a globally distributed and dispatchable fuel network to contribute to political, economic, social, environmental, fuel and climate security [ 7 ]. Current first-generation biofuel technologies, reliant on food crops, such as bioethanol from corn or sugar and biodiesel from soy or palm oil, compete with food production for arable land and fresh water and contribute to eutrophication [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%